(2cosx+1)(cosx−1)=0,
so solve each for when either equals 0,
cosx−1=0 when x=360n, and 2cosx+1=0 when x=360n±120
'n' being any positive/negative integer
2007-06-19 09:24:08
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
You could also do the substitution y=cos(x) so that it simplifies to something you are probably more familiar with...
2y^2+y-1....... solve with quadratic equation and then solve back for x using y=cos(x) after youve solved for y.
also, from above, assuming this whole thing equals zero
(2*cos(x)- 1)*(cos(x)+1)=0
then the solutions are cos(x) = 1/2 and cos(x) = -1
note that there are actually an infinite number of solutions
cos(x) = 1/2 => x = pi/6 + 2*n*pi and x = -pi/6 + 2*n*pi for n=0,1,2,3....infinity
same thing for cos(x) = -1
2007-06-19 08:50:36
·
answer #2
·
answered by Anonymous
·
1⤊
0⤋
2cos^2x + cos x - 1
= (2Cos x-1) (Cos x+1)
this is an expression and not an equation...
so there wont be a solution
2007-06-19 08:29:39
·
answer #3
·
answered by Surendra G 1
·
1⤊
1⤋
Factor it: (2cosx + 1)(cosx - 1) = 0.
2cosx + 1 = 0 --> cos(x)=0.5, so x=arccos(0.5) = (pi/3) (considering only a simple answer).
cos(x) - 1 = 0 --> cos(x) = 1 --> x = 0.
There are infinitely many answers due to the periodicity of cos(x).
2007-06-19 08:29:24
·
answer #4
·
answered by Mathsorcerer 7
·
0⤊
2⤋
2cos^2x+cosx-1=0
2cos^2x+2cosx-cosx-1
=2cosx(cosx+1)-1(cosx+1)=0
(cosx+1)(2cosx-1)=0
cosx=1,-1/2
x=0,120,240deg
=0,2pi/3, 4pi/3.answer
2007-06-19 08:44:02
·
answer #5
·
answered by Anonymous
·
2⤊
0⤋